Extracellular lipolytic activity in Phoma glomerata - Pollero, Ricardo José (2001)
Several properties of the lipolytic activity exhibited by the conidial fungus Phoma glomerata were studied. Lipolytic activity in an aqueous buffer medium was measured on triacylglycerol, phosphoglyceride and cholesterol ester under different experimental conditions. The effect of storage temperature on the stability of the hydrolytic activity, and optimal conditions of temperature and time of maximal activity were determined. The optimal conditions for maximal lipolytic activity were found to be 40–50 °C and 1 h. The activity released to the medium by 1 mg cells for 1 h at 40 °C was stated as the enzyme released unit (ERU). The protein fraction of MW > 50 kDa obtained by ultrafiltration of the medium, was active on the three substrates assayed, and it showed a non-specific hydrolytic activity on both the 1- and 2-acyl esters either in the neutral glyceride or in the phosphoglyceride. A protein of Mr approx. 75 kDa was the only one that showed esterase activity. The crude medium, stored at −15 °C, maintained its initial hydrolytic activity on triacylglycerol for at least 42 days, though when it was kept for 10 days at 4 °C, the activity fell to 50%. Kinetic parameters using substrates such as triolein (TO), dipalmitoyl phosphatidylcholine (DPPC) and cholesteryl oleate (ChoO), were comparatively evaluated. The activity of the enzyme in the hydrolysis of TO showed the highest values, whereas the maximal specific activities were less when the enzyme was assayed against DPPC and ChoO.